Characterization of soil nematode community structure in semi‐arid dryland barley systems. Issue 3 (20th June 2022) - Burkhardt, Andy; Briar, Shabeg; Martin, John M.; Carr, Patrick M.; Sherman, Jamie
Abstract: Soil nematode community structure and composition can inform crop managers about soil quality. However, few studies have assessed the nematode community under agricultural systems in cool semi‐arid regions such as the U.S. northern Great Plains. We assessed soil nematode community structure of barley ( Hordeum vulgare L.) and barley–pea ( Pisum sativum L.) cropping systems from 2016 to 2018 in one tilled and two no‐till field experiments under dryland management in central and southwestern Montana. Soils were sampled prior to planting in the spring and following harvest in late summer and nematodes were classified to genus level via microscopy. Both in season moisture stress and overwinter stress explained decline in nematodes in the central Montana no‐till experiments, although consistent impacts of moisture or overwinter stress on nematodes were not detected in the tilled field experiment. Cropping system or sequence did not impact the nematode population ( p  > .1), but barley yield was positively correlated with larger nematode populations in both no‐till experiments ( r  > .60). The percentage of fungivores were negatively correlated ( r  = –.42) to barley yield under tillage. Plant parasitic nematodes were positively correlated ( r  = .43) to barley yield under tillage. These results suggest that factors which enhance cereal crop growth and productivity rather than crop diversification drive short‐term nematode community dynamics when crop rotations are established in cool semi‐arid regions. Future work is needed to determine if cropping system changes can impact nematode populations after several years in cool semi‐arid regions and, if so, what ecosystem services result from these transformations. Core Ideas: Nematode community dynamics were assessed in barley‐dominated cropping systems. Herbivorous nematode (PPN) populations were positively correlated with barley yields. Moisture stress was a significant driver in nematode community dynamics.